COMPARATIVE STUDY OF ORAL ANOMALIES, DECAYED, MISSING, FILLED TEETH (DMFT), ORAL HYGIENE INDEX-SIMPLIFIED (OHI-S) AND PARA-FUNCTIONAL HABITS (PFH) AMONG SCHOOL AND STREET CHILDREN OF ISLAMABAD - Rabia Masood; Noor Ul Ain Hassan; Seema Shafiq; Amber Kiyani; Sara Haq; Amara Butt; Alina Hassan; Raahima Hussain; Ania Mehr; Ammara Zulfiqar (Pakistan Oral & Dental Journal, 2022)
Due to modern eating habits and subsequent increase in sugar intake, the pediatric population seeking dental care has shown significant increase among children attending schools in comparison to street children. The purpose of this study was to compare prevalence of congenital anomalies, decayed, missing, filled teeth (DMFT) scores, oral hygiene index (OHI-S) and parafunctional habits (PFH), and oral anomalies among school and street children. A cross-sectional study design was used to record data from 250 children in the out-patient clinics at Islamic International Dental College (group A) and from 250 children kept out of schools (group B). The children were between 5 to 15 years (mean=11.17+/-3.14). The information was recorded on pre-drafted proformas following consent, history and oral examination. Results were analyzed using SPSS version 23.0. Chi-square test and independent T-test were used to compare the two populations (p<0.05). Significant statistical differences were noted between the DMFT and OHI-S indices of school and street children (p=0.02 and p<0.01, respectively). A higher prevalence of PFH was noted in school children while anomalies were noted in both groups. Differences in DMFT scores, OHI-S, PFH and oral anomalies was noted between children going to school and street children.